Spontaneous Rupture of Kidney Due to Posterior Urethral Valve–Diagnostic Difficulties - Kiliś-Pstrusińska, Katarzyna (Tehran University of Medical Sciences, 2013)
BACKGROUND: Spontaneous kidney rupture could develop in the course of posterior urethral valve (PUV), the most common cause of outflow urinary tract obstruction in male infants. However, urinary extravasation is a rare complication among this group of children. CASE PRESENTATION: Our case report presents diagnostic difficulties connected with spontaneous kidney rupture due to PUV in a 6 week-old infant. Due to not equivocal images, thundery course of disease and rapid deterioration in the infant's condition, the patient required an urgent laparatomy. CONCLUSION: This case showed that the investigation of renal abnormalities during early neonatal period, is very important specifically in PUV that can lead to kidney rupture.